Acute heart failure syndrome in the elderly. Issue 3 (9th October 2017) - Katsanos, S.; Bakosis, G.; Frogudaki, A.
Abstract: Acute heart failure (AHF) in the elderly is becoming an increasingly common clinical problem, associated with very high in‐hospital and long‐term mortality rates. Elderly AHF patients, as opposed to younger ones, may have a different demographic, pathophysiological, clinical, and prognostic profile, and therefore, some carefully considered therapeutic adjustments may be warranted for their treatment. Patients with older age, shock, diabetes, renal failure, infection, confusion, and severe non‐cardiac comorbidities may be at the highest mortality risk. Answer questions and earn CME:https://wileyhealthlearning.com/Activity2/5608945/Activity.aspx